Karakteristik Populasi Labi-labi Amyda cartilaginea (Boddaert, 1770) yang Tertangkap di Sumatera Selatan - Sentosa, Agus Arifin; Wijaya, Danu; Suryandari, Astri (Perhimpunan Biologi Indonesia, 2013)
The Asiatic softshell turtle Amyda cartilaginea (Boddaert, 1770) is one of the reptile commodities included in CITESAppendix II with vulnerable status according to IUCN. The species has been harvesting, especially for export purposein South Sumatera. The reseach was aimed to know the population characteristics of the Asiatic softshell turtleharvested in South Sumatera. The study was carried out based on enumerators approach from July to Desember2012 in South Sumatera. The data enumeration also has been collected from the 1st collectors. Data analysis includedthe size distribution of carapace curve length (CCL), carapace curve width (CCW), body weight, sex ratio, agestructure, CCL-weight relationship and von Bertalanffy growth parameters. The results showed that there wererecorded 306 individuals of A. cartilaginea (92% adult) with sex ratio male and female is 42:58. Its has carapacecurve length range from 10 to 75.5 cm, carapace curve width 9 to 59.5 cm and body weight 0.02 to 40 kg. A.cartilaginea growth pattern was negatively allometric (b = 2.727). The von Bertalanffy growth formula of A.cartilaginea in South Sumatera was PLK(t) = 78,751-exp[-0,18(t-(-0,72)] cm.Keywords: Amyda cartilaginea, population characteristics, South Sumatera